Navigating secondary breast angiosarcoma: a case report - Marina Balbino; Manuela Montatore; Federica Masino; Francesca A. Carpagnano; Giuseppe Guglielmi (Digital Diagnostics)
We describe a rare case of secondary breast angiosarcoma in a 72-year-old woman with a history of breast cancer who presented to our clinic with a painless palpable mass in the outer upper quadrant of the left breast. The diagnosis required a multidisciplinary approach involving a senologist, anatomopathologist, and oncologist. Imaging modalities such as mammography, ultrasonography, and magnetic resonance imaging made it possible to assess the extent of the tumor, lymph node involvement, and distant metastases. The diagnosis was confirmed by a tissue biopsy. Herein, a rare case is presented, with the main educational purpose of describing the clinical presentation and complex diagnostic evaluation and discussing the differential diagnosis and management. Indeed, secondary mammary angiosarcoma is a rare and aggressive neoplasm, and understanding its unique features is essential for clinical decision-making and patient outcomes. The tumor has a worse prognosis because of its late diagnosis, higher risk of rapid distant spread, and limited treatment options. Such cases require close monitoring, aggressive strategies, and supportive care.